Molecular Characterization of Intestinal Microsporidia in Immunocompromised Patient in THI-QAR Province - Khalid Jameel Kadhim Al-Zihiry, Saleem Abdul Amir Jaber Alshuwaili (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Immunocompromised host has one or more defects in the normal defense mechanisms that protect against infectious agents. Microsporidia are group of protozoa characterized via obligate intracellular and spore formation, detected in many hosts. Up till now, 1300 microsporidia species or more, related to 150 genera, were, microsporidiosis caused by microsporidia. Objectives: To conduct Molecular characterization of intestinal microsporidia in immunocompromised patient in Thi-Qar province cases. Patients and Methods: Totally, two hundred stool samples were collected and subdivided into 185 cancer patients and 15 organ transplantation patients. Samples were examined for microsporidiosis by light microscopy smears stained by Chromotrope Kenyon stain and by PCR techniques. Results: using Polymerase chain reaction technique (PCR), microsporidia were detected in eleven sample out of 116 sample that were positive by microscopic examination and Chromotrope Kenyon stain. Positive sample by PCR were sent for sequencing and the result showed that the samples of the current study were similar to three microsporidia, Enterocytozoon bieneusi, Encephalitozoon cuniculi and Encephalitozoon intestinalis. Conclusion: The present study confirmed the presence of Microsporidia infection is among immunocompromised patients. Keyword: Molecular, immunocompromised , microsporidia, PCR